Analysing the role of the perceptual dimension in the formation of the urban third place - Upendra Joshi; Snehal Nagarsheth (Enquiry: The ARCC Journal of Architectural Research)
Urban third places like parks, plazas, and cafes play a significant role in fostering social interaction, community engagement, and a sense of belonging in contemporary society, and this recognition is growing. It has been a subject of critical analysis across multiple disciplines and intellectual traditions. Although the term 'Third Place' has been the subject of considerable research for some time, a sensible investigation into the psychological needs of users broadens the study's scope, adding a new dimension to the research. This study's perceptual dimension focuses particularly on an individual's perceptions of the built environment of the urban third place.